Surface roughness of heat treated Eucalyptus grandis wood - Pires de Moura Palermo, Gilmara; de Figueiredo Latorraca, João Vicente; de Moura, Luiz Fernando; Nolasco, Adriana Maria; Monteiro de Carvalho, Alexandre; Garcia, Rosilei Aparecida (Maderas. Ciencia y Tecnología, 2025)
This study aimed to evaluate surface roughness of heat treated Eucalyptus grandis wood after peripheral planning and sanding performed in directions to the grain and against the grain. For machining tests, workpieces were collected from two different regions in the radial direction, as follows: internal, nearby the pit; external, nearby the bark. Heat treatment was carried out by heating samples at a maximum temperature of 190ºC, with total treatment duration of 390 minutes. Heat treated and control samples underwent peripheral planning and sanding tests. The quality of machined surfaces was assessed by means of roughness average (Ra) measurements across and along the grain orientation. Results indicated significant differences in surface roughness as a function of machining feed direction, sandpaper grit size, and heat treatment. Surface roughness has not shown any difference in the radial direction.